Food52 your do-anything kitchen : the trusty guide to a smarter, tidier, happier space - Ransom, James (Photographer) (Ten Speed Press, 2020)
Provides ideas for setting up, organizing and enjoying a perfect kitchen from what essential tools and ingredients to always have on hand, to organizing storage container clutter and maximizing drawer and counter space.